Co-delivery of doxorubicin and siRNA for glioma therapy by a brain targeting system: angiopep-2-modified poly(lactic-co-glycolic acid) nanoparticles. (21st October 2015) - Wang, Lei; Hao, Yongwei; Li, Haixia; Zhao, Yalin; Meng, Dehui; Li, Dong; Shi, Jinjin; Zhang, Hongling; Zhang, Zhenzhong; Zhang, Yun
Abstract: It is very challenging to treat brain cancer because of the blood–brain barrier (BBB) restricting therapeutic drug or gene to access the brain. In this research project, angiopep-2 (ANG) was used as a brain-targeted peptide for preparing multifunctional ANG-modified poly(lactic- co -glycolic acid) (PLGA) nanoparticles (NPs), which encapsulated both doxorubicin (DOX) and epidermal growth factor receptor (EGFR) siRNA, designated as ANG/PLGA/DOX/siRNA. This system could efficiently deliver DOX and siRNA into U87MG cells leading to significant cell inhibition, apoptosis and EGFR silencing in vitro . It demonstrated that this drug system was capable of penetrating the BBB in vivo, resulting in more drugs accumulation in the brain. The animal study using the brain orthotopic U87MG glioma xenograft model indicated that the ANG-targeted co-delivery of DOX and EGFR siRNA resulted in not only the prolongation of the life span of the glioma-bearing mice but also an obvious cell apoptosis in glioma tissue.